EFFECTIVENESS OF CALCIPOTRIOL VERSUS BETAMETHASONE DIPROPIONATE IN THE TREATMENT OF MILD TO MODERATE CHRONIC PLAQUE PSORIASIS - Ali, Safdar; Noor, Sahibzada Mahmood; Zahoor, Hina; Majid Paracha, Mohammad (Journal of Postgraduate Medical Institute, 2018)
Objective: To compare the effectiveness of calcipotriol versus betamethasone dipropionate in the treatment of mild to moderate chronic plaque psoriasis. Methodology: A total of 112 patients with mild to moderate psoriasis were enrolled in this randomized controlled trial. These patients were randomly allocated into two groups (A and B) by lottery method. Betamethasone dipropionate was given to group A, while calcipotriol was given to group B. Response to treatment was assessed on the basis of 50% reduction in psoriasis area and severity index (PASI) score after 4 weeks of topical treatment. SPSS version 21 for Windows was used for data entry and analysis. Results: In group A, Betamethasosne was effective in 44 patients (78.57%), while it was not effective in 12 patients (21.43%). In group B, calcipotriol was effective in 41 patients (73.21%). while it was not effective in 15 (26.79%). The P value was 0.659 which was statistically not significant. Conclusion: Both betamethasone dipropionate and calcipotriol were found effective in mild to moderate forms of chronic plaque psoriasis. Calcipotriol has comparable effectiveness to betamethasone dipropionate.